Indução de variabilidade genética aplicada ao melhoramento de Braquiária - Follmann, Diego Nicolau (2014)
The application and adaptation of pre-selection techniques to select individuals with traits of interest is of high importance with the breeding programs, as well as the gain selection in the populations studied. In populations that survived the pre-selection and middle selection, study the dissimilarities in genotypes is of high importance in order to identify and select superior individuals. The aim of this work is to study the effect of chemical induction of mutation with respect to the emergence of genetic variability in apomictic Brachiaria Brizantha genotypes, with the applying pre-selection for cold tolerance by calculating the estimated gain of selection within and among populations, also to behave studies on the dissimilarity of the mutants and commercial subjects after passing the scrutiny of environmental selection in two years of cultivation. The study was conducted in the city of Frederico Westphalen-RS, at the Laboratory of Genetic Breeding and Plant Production, UFSM. The study was behaved in a population of genotypes formed after chemical induction of Methyl Methane Sulfonate 0.5% in 50.000 seeds of commercial genotypes, that after soaking mutagen initiated germination and development process at low temperatures, which result in transplanted to field conditions for exposure selection, depending on the environmental conditions present in the environment in question. Survivors to scrutiny selective formed population of 35 individuals, which seeds were collected in his descendants for studies in M2 and M3 generations. Under conditions of controlled chamber was applied pre-selection of individual levels of cold 1 ° C, 0 ° C, 1 ° C and 2 ° C and 3 ° C in the same associations at 5 ° C to verify the response of genotypes, calculating the estimated gain selection within and among populations. Proceeded to study the genetic dissimilarity of accesses according to 21 variables by averaging Euclidian distance to verify genetic variability generated after chemical induction of mutation and selection of the medium on the genotypes. The pre-selection may be induced to select individuals with predisposition to tolerance at all levels of cold, however the selection gain was higher in the levels of cold 0 ° C and 1 ° C in association with extreme cold, so among populations the M2 generation had greater gain selection to the M3 generation due to higher this selection. There was high dissimilarity among genotypes studied, the 38 subjects studied was formed 18 groups. Of the 35 mutant genotypes, only one clustered together with the three commercial witness, indicating that the mutation induced genotypes better adaptation to growth at low temperatures and inflorescence production.